MEMBANGUN KEUNGGULAN BERSAING DENGAN STRATEGI PRODUKSI JOB LOT SHOP PADA USAHA SEPEDA CUSTOM PUSAT BIKE - Lubis, Moch. Dhanu; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Creating competitive advantage is a strategy by businesses to win the competition. A company must have some distinctive leverages which are not owned by its competitors to win the competition and to avoid business failures. Pusat Bike runsa custom bicycle business that has been planned with some future competitive advantages. Established in 2019, this business is prospective fromall sides. In order to develop the business, the company applies job lot shop production strategy to reduce inventory and improve quality. This strategy uses mixed flow process, in which the products are manufactured in intermittent interval batches. Here tools and labors are organized into work centers based on the task. Pusat Bike has established a production specialist teams; each team focuses on one type of bicycle product. This method simplifies the inventory estimation for each bicycle type. It also useful for efficiency because the team that has been assigned to a certain type of bicycle can improve faster and produce more quickly, ensuring efficient production process. Team divisions based on the product type also enhances product quality, which correlates with consumer satisfaction.